Deposition Of Nylon Membrane On Carbon Electrode For The Development Of Ascorbic Acid Electrochemical Biosensor - Harith, Noor Nadhirah (Universiti Sains Malaysia, 2018)
Electrochemical biosensor is the combination of electroanalytical methods of high sensitivity with a presence of biorecognition system that helps in identifying target species. The main objective of this work is to study the conjugation of ascorbic acid (AA) to polyaniline (PANI) and to explore the cyclic voltammetry and electrochemical impedance spectroscopy of the membrane-based sensor to detect AA. In this study, the conjugation of ascorbic AA was first done by the synthesis of PANI/Fe2O3, before the AA was interacted with PANI/Fe2O3. UV-Vis spectrometer absorbance for solutions PBS, AA of 50 mM, PANI, PANI/Fe2O3 and PANI/Fe2O3/AA of 50 mM were measured to prove the successful conjugation of AA. Next, membrane-sensor was assembled, bare glass carbon electrode (GCE), GCE-nylon membrane and GCE-nylon membrane immobilized with ascorbate oxidase were testing with AA. The cyclic voltammetry pattern and electrochemical impedance spectroscopy were recorded to study the redox potential and conductivity of the testing solutions.